SURVEY OF MEDICATION ADHERENCE AND ASSOCIATED FACTORS AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS AT SAINT-PAUL GENERAL HOSPITAL IN 2025 - Nguyen Van Trieu,; Nguyen Dinh Hien,; Tran Thanh Huyen,; Nguyen Kieu Tra My, (Tạp chí Y học Quân sự, 2026)
Objectives: To assess the level of medication adherence and associated factors among patients with type 2 diabetes mellitus. Subjects and methods: A descriptive cross-sectional study was conducted among 279 patients with type 2 diabetes mellitus who were examined and treated at Saint-Paul General Hospital from June to December 2025. Medication adherence was assessed using the 8-item Morisky Medication Adherence Scale (MMAS-8). Associated factors were identified using multivariable binary logistic regression analysis. Results: The proportions of patients with good, moderate, and poor medication adherence were 28.0%, 41.2%, and 30.8%, respectively. The most common non-adherent behavior was occasionally forgetting to take blood glucose-lowering medication (68.1%). Multivariable binary logistic regression analysis showed four factors independently associated with medication adherence. The adherence rate among patients using insulin was significantly lower than that among those not using insulin (aOR = 0.287; 95% CI: 0.134-0.612; p = 0.001). Patients who achieved blood glucose targets, HbA1c control, and engaged in physical exercise had significantly higher adherence rates than those who did not achieve blood glucose targets (aOR = 3.306; 95%CI: 1.316-8.306; p = 0.011), had HbA1c ≥ 7% (aOR = 0.058; 95% CI: 0.007-0.481; p = 0.008), and did not engage in physical exercise (aOR = 5.620; 95% CI: 2.194-14.396; p < 0.001). Conclusions: Patients with type 2 diabetes mellitus examined and treated at Saint-Paul General Hospital had a relatively low rate of medication adherence. Insulin use, blood glucose control, HbA1c control, and physical activity were independent factors associated with medication adherence. Strengthened counseling, health education, and adherence-support interventions are needed for patients.